1994
DOI: 10.1016/0006-2952(94)90287-9
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of proteins by artemisinin

Abstract: Artemisinin and its derivatives are a promising new class of antimalarial agents containing an endoperoxide bridge. [14C]Artemisinin alkylated various proteins in vitro. Between 5 and 18% of added drug bound to hemoproteins such as catalase, cytochrome c, and hemoglobin. However, it did not react with heme-free globin. For catalase and hemoglobin, most of the drug reacted with the protein moiety rather than the heme. Artemisinin bound to human serum albumin (HSA) more efficiently at pH 8.6 than 7.4, more effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(21 citation statements)
references
References 17 publications
(5 reference statements)
1
20
0
Order By: Relevance
“…8,12,5052 For example, depending on the experimental model, some drug derivatives concentrate in the endoplasmic reticulum while others localize in the mitochondrion. 51 It seems a consensus, based on the structure-function relationship of this class of compounds, 52 that artemisinins do not bind specific targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,12,5052 For example, depending on the experimental model, some drug derivatives concentrate in the endoplasmic reticulum while others localize in the mitochondrion. 51 It seems a consensus, based on the structure-function relationship of this class of compounds, 52 that artemisinins do not bind specific targets.…”
Section: Discussionmentioning
confidence: 99%
“…11 These reactive molecules can alkylate thiols and amine moieties of albumin 8 as well as other proteins. 12 However, definitive evidence is lacking to show that this process mediates the activity of artemisinins in non-malarial disease conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This phenotype is correlated with mutations in the P. falciparum Kelch13 gene [13, 14, 16, 17] and changes in both signalling pathways [1821] and organellar function [2229]. Overall, due to the complexity of artemisinin’s mechanism of killing (see citations above and [30–36]), it has been challenging to separate the causes and effects of resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Other researchers have focused on the interactions of artemisinins with specific target proteins. [12][13][14] An early clue to the involvement of iron in the activation mechanism came from studies which showed that the antimalarial activity of artemisinin is strongly antagonized by iron chelators. [15] Since the chelators used in this earlier study are selective for non-heme sources of iron, it is apparent that chelatable parasite iron sources may have an important role to play in the mechanism of action of endoperoxidebased antimalarial drugs.…”
mentioning
confidence: 99%